Ethical dilemmas in the global defense industry - Schoeni, Daniel E.; Vestner, Tobias (New York, NY : Oxford University Press, 2023)
The defense industry develops, produces, and sells weapons that cause great harm. It operates at the intersection of the public and private sectors, with increased reliance on technology companies. This book brings together the diverse perspectives of scholars and practitioners from academia, government service, the military, and the private sector to discuss the moral and legal challenges facing the global defense industry and to introduce solutions that are innovative, effective, and practical.
Also issued in print: 2023.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 24, 2023).
Keywords: Defense industries -- Moral and ethical aspects; Defense industries -- Law and legislation; Society; Ethics & moral philosophy